MP2C, a plant protein phosphatase 2C, functions as a negative regulator of mitogen-activated protein kinase pathways in yeast and plants - Meskiene, Irute (The National Academy of Sciences, 1998)
By interference of the yeast pheromone mitogen-activated protein kinase (MAPK) pathway with an alfalfa cDNA expression library, we have isolated the MP2C gene encoding a functional protein phosphatase type 2C. Epistasis analysis in yeast indicated that the molecular target of the MP2C phosphatase is Ste11, a MAPK kinase kinase that is a central regulator of the pheromone and osmosensing pathways. In plants, MP2C functions as a negative regulator of the stress-activated MAPK (SAMK) pathway that is activated by cold, drought, touch, and wounding. Although activation of the SAMK pathway occurs by a posttranslational mechanism, de novo transcription and translation of protein factor(s) are necessary for its inactivation. MP2C is likely to be this or one of these factors, because wound-induced activation of SAMK is followed by MP2C gene expression and recombinant glutathione S-transferase–MP2C is able to inactivate extracts containing wound-induced SAMK. Wound-induced MP2C expression is a transient event and correlates with the refractory period, i.e., the time when restimulation of the SAMK pathway is not possible by a second stimulation. These data suggest that MP2C is part of a negative feedback mechanism that is responsible for resetting the SAMK cascade in plants.